Guided Double Cantilever Beam test method for intermediate and high loading rates in composites. (1st March 2023) - Medina, S.A.; González, E.V.; Blanco, N.; Pernas-Sánchez, J.; Artero-Guerrero, J.A.
Abstract: Although the rate-dependent behaviour of the interlaminar fracture toughness of fibre reinforced composites has been a matter of ongoing research in recent decades, further research is required into characterising these properties and, consequently, developing more reliable constitutive models to simulate dynamic events. Furthermore, despite the various studies that have been carried out, no consensus on which test method to use to characterise these properties has yet been reached. This paper presents a new test method for measuring the dynamic mode I interlaminar fracture toughness in composite laminates by using a novel device based on a modified Double Cantilever Beam test method with a guided tensile configuration. In contrast to other methods reported in the literature, the proposed device guarantees a symmetric crack opening and, thus, pure mode I propagation during high loading rate testing. When used in a dynamic servo-hydraulic testing machine with controllable displacement rate, a constant opening velocity can be achieved. The Guided Double Cantilever Beam testing method is validated against a quasi-static Double Cantilever Beam test, showing good agreement between the results. The testing method has been satisfactorily tested under intermediate/high loading rates, from 0.1 to 10 m/s. Highlights: A new test method to measure the dynamic mode I interlaminar fracture toughness in composite is presented. A pure mode I is achieved with the testing tool by a symmetric crack opening. The GDCB method proposed allows constant opening velocity at the loading points. The method avoids impact events and the friction between the tool and the inner surface of the specimen crack.